Subchondral injection of human umbilical cord mesenchymal stem cells ameliorates knee osteoarthritis by inhibiting osteoblast apoptosis and TGF-beta activity - Congzi Wu; HuiHui Xu; Zhen Wu; Haipeng Huang; Qinwen Ge; Jianbo Xu; Jiali Chen; Pinger Wang; Wenhua Yuan; Hongting Jin; Peijian Tong (Stem Cell Research & Therapy)
Abstract Background Osteoarthritis (OA) is a common degenerative disease caused by multiple pathological mechanisms wherein subchondral bone malfunction plays a substantial role. Recently, subchondral (SC) injection of orthobiologics has been attracting growing interest albeit the mainstream delivery method of mesenchymal stem cells (MSCs) is through intra-articular (IA). This study investigates the effect of SC injection of human umbilical cord mesenchymal stem cells (UCMSCs) on OA and its possible therapeutic mechanism compared to IA injection. Methods Male Sprague-Dawley rats with anterior cruciate ligament transection (ACLT) received saline or UCMSC injections via SC or IA. Consecutive injections once a week for three weeks and withdrawal for another four weeks, followed by Radiographical scanning, histopathological, immunohistochemical, and terminal deoxynucleotidyl transferase (TdT)-mediated dUTP nick-end labelling (TUNEL) staining. Cell counting Kit-8 (CCK-8) assay, alkaline phosphatase (ALP), alizarin red staining (ARS), TUNEL, flow cytometry, quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting were employed in TNFα-induced MC3T3-E1 cells to illustrate the exact pathogenesis mechanism. Results IA and SC UCMSC injections preserved cartilage, synovium, and subchondral bone parameters like trabecular bone volume fraction (BV/TV). SC injection uniquely improved Trabecular separation (Tb.Sp) and Trabecular number (Tb.N). SC and IA injections of UCMSCs demonstrated equivalent efficacy in promoting osteoblastic bone formation and attenuating aberrant angiogenesis of subchondral bone. In addition, we demonstrated that osteoblast apoptosis and Smad2-dependent TGF-beta (TGF-β) are crucial and interactive subchondral bone pathological features in OA. In vivo and vitro studies further revealed that UCMSCs inhibited excessive TGF-β/pSmad2 signaling to regulate aberrant vascularization, osteoblast apoptosis and differentiation imbalance, ultimately maintaining osteochondral homeostasis. Conclusions The efficacy of UCMSCs for treating OA rats via SC injection was equivalent to that of IA; and even superior to IA in terms of subchondral bone phenotype via regulating apoptosis and TGF-β/pSmad2 signaling in osteoblasts, suggesting SC injection of UCMSCs as a potential and promising cell therapy for OA treatment.